Gene Expression Changes and Associated Pathways Involved in the Progression of Prostate Cancer Advanced Stages - Pudova, Elena A.; Krasnov, George S.; Kobelyatskaya, Anastasiya A.; Savvateeva, Maria V.; Fedorova, Maria S.; Pavlov, Vladislav S.; Nyushko, Kirill M.; Kaprin, Andrey D.; Alekseev, Boris Y.; Trofimov, Dmitry Y.; Sukhikh, Gennady T.; Snezhkina, Anastasiya V.; et al. (Frontiers in Genetics, 2021)
Prostate cancer is one of the most common socially significant tumors. Advanced stages of prostate cancer, such as locally advanced and castration-resistant prostate cancer, are present the greatest clinical management problem. Known indicators exhibit low capacity to predict the disease course, therefore these categories of prostate cancer need better prognostic markers. In the study, we performed a bioinformatic analysis of The Cancer Genome Atlas (TCGA) data, including the RNA-Seq data of the PRAD (n = 55) and WCDT-MCRPC (n = 84) projects for searching of transcriptome changes associated with the progression-free survival for locally advanced and castration-resistant prostate cancer, respectively. We identified genes, which expression was positively/negatively correlated with progression-free survival for each dataset. The most significant correlations were shown for SOD3, ZC2HC1A, LRRC26, SLE, and KIF11 genes in locally advanced prostate cancer as well as for BET1, CTAGE5, IFNGR1, GIMAP6, CLPB, PRPF19, ZNF610, and MPST genes in castration-resistant prostate cancer. Also, we performed gene network interaction analysis using STRINGdb that revealed a significant relationship between genes predominantly involved in the cell cycle and characterized by up-regulation of their expression in the early recurrence. Following obtained results we supposed several genes that can be used as potential prognostic markers.